Palladium‐Catalyzed Enantioselective C−H Olefination of Diaryl Sulfoxides through Parallel Kinetic Resolution and Desymmetrization. Issue 18 (23rd March 2018) - Zhu, Yu‐Chao; Li, Yan; Zhang, Bo‐Chao; Zhang, Feng‐Xu; Yang, Yi‐Nuo; Wang, Xi‐Sheng
Abstract: The first example of Pd II ‐catalyzed enantioselective C−H olefination with non‐chiral or racemic sulfoxides as directing groups was developed. A variety of chiral diaryl sulfoxides were synthesized with high enantioselectivity (up to 99 %) through both desymmetrization and parallel kinetic resolution (PKR). This is the first report of Pd II ‐catalyzed enantioselective C(sp 2 )−H functionalization through PKR, and it represents a novel strategy to construct sulfur chiral centers. Abstract : A Pd II ‐catalyzed enantioselective C−H olefination with non‐chiral or racemic sulfoxides as directing groups was developed. A variety of chiral diaryl sulfoxides were synthesized with high enantioselectivity through both desymmetrization and parallel kinetic resolution (PKR). This is the first reported Pd II ‐catalyzed enantioselective C(sp 2 )−H functionalization through PKR, and it represents a novel strategy to construct sulfur chiral centers.